An In Situ Polymerized Comb-Like PLA/PEG-based Solid Polymer Electrolyte for Lithium Metal Batteries. Issue 7 (1st January 2020) - Zaheer, Muhammad; Xu, Hongli; Wang, Bingbing; Li, Lianwei; Deng, Yonghong
Abstract : High ionic conductivity is a prerequisite for the application of solid-state polymer electrolyte towards the safe and high energy density electrochemical devices. Here we report the preparation and properties of an in-situ polymerized comb-like copolymer-based SPE (PLA/PEG-SPE) with high ionic conductivity from methyl acrylate functionalized poly(D, L-Lactide) (PLAMA) and poly(ethylene glycol) methyl ether methacrylate (PEGMA). A remarkably high ionic conductivity value of 6.9 × 10 −5 S cm −1 at ambient temperature and a maximum ionic conductivity of 4.3 × 10 −4 S cm −1 at 60°C were detected, with an activation energy of 0.2 eV and a Li + transference number (tLi + ) of 0.36. The PLA/PEG-SPE exhibits a wide electrochemical stability window up to 4.6 vs. Li/Li + and very good lithium metal electrode compatibility. Solid-state LiFePO4 /SPE/Li cells with integrated cathode and lithium metal deliver superior cycling stability with high discharge capacities (149 mAh g −1 as the initial specific capacity) and high capacity retention (exceeded 82% of its initial specific capacity) at 0.2 C at 60°C. The solid-state cells are also capable of being cycled at room temperature at 0.2 C. This work highlights a facile, in-situ fabrication strategy involving a vinyl-functionalized PLA precursor that yields a high-performance ion-conducting membrane attractive for lithium metal battery applications.